Race-Based Differences in Lipoprotein(a)-Associated Risk of Carotid Atherosclerosis: The Multi-Ethnic Study of Atherosclerosis. Issue 3 (March 2019) - Steffen, Brian T.; Thanassoulis, George; Duprez, Daniel; Stein, James H.; Karger, Amy B.; Tattersall, Mathew C.; Kaufman, Joel D.; Guan, Weihua; Tsai, Michael Y.
Abstract : Objective—: Lp(a) [lipoprotein(a)] is a well-described risk factor for atherosclerosis, but Lp(a)-associated risk may vary by race/ethnicity. We aimed to determine whether race/ethnicity modifies Lp(a)-related risk of carotid atherosclerotic plaque outcomes among black, white, Chinese, and Hispanic individuals. Approach and Results—: Carotid plaque presence and score were assessed by ultrasonography at baseline (n=5155) and following a median 9.4 year period (n=3380) in MESA (Multi-Ethnic Study of Atherosclerosis) participants. Lp(a) concentrations were measured by immunoassay and examined as a continuous and categorical variable using clinically-based cutoffs, 30 and 50 mg/dL. Lp(a) was related to greater risk of prevalent carotid plaque at baseline in whites alone (all P <0.001): per log unit (relative risk, 1.05); Lp(a)≥30 mg/dL (relative risk, 1.16); and Lp(a)≥50 mg/dL (relative risk, 1.20). Lp(a) levels over 50 mg/dL were associated with a higher plaque score at baseline in whites (all P <0.001) and Hispanics ( P =0.04). In prospective analyses, whites with Lp(a) ≥50 mg/dL were found to have greater risk of plaque progression (relative risk, 1.12; P =0.03) and higher plaque scores (all P <0.001) over the 9.4-year follow-up. Race-based differences between whites and black participants were significant for cross-sectional associations and for carotid plaque score following the 9.4 year study period. Conclusions—: Race was found to be a modifying variable in Lp(a)-related risk of carotid plaque, and Lp(a) levels may have greater influence on plaque burden in whites than in black individuals. Borderline results in Hispanics suggest that elevated Lp(a) may increase the risk of carotid plaque, but follow-up studies are needed. Abstract : Supplemental Digital Content is available in the text.